ANALYSIS OF THE APPLICATION OF LOCAL WISDOM OF NIAS IN PROBLEM-BASED LEARNING: A LITERATURE REVIEW WITH A DESCRIPTIVE APPROACH - Natalia Kristiani Lase; Bornok Sinaga; Retno Dwi Suyanti (Research on English Language Education, 2025)
Local wisdom plays a vital role in preserving cultural identity, fostering social harmony, and strengthening a community’s sense of belonging. Within the educational context, integrating local wisdom into learning activities creates meaningful connections between theoretical knowledge and the cultural realities experienced by students in their daily lives. This approach not only promotes contextual learning but also nurtures students’ appreciation of their heritage. This article explores the incorporation of Nias local wisdom into the Problem-Based Learning (PBL) model as a strategy to enhance both academic achievement and character formation. The Nias community possesses rich traditions, social values, and problem-solving practices rooted in cooperation, respect, and responsibility. By embedding these elements into the PBL framework, students are encouraged to engage in authentic learning experiences that mirror real-life challenges while reflecting their cultural identity. The findings show that the integration of Nias local wisdom within PBL significantly improves students’ cognitive, affective, and social competencies. Students demonstrate increased motivation, collaboration, and critical thinking, while also developing empathy and respect for cultural diversity. Moreover, this approach enriches the learning environment by linking education to the community’s cultural context. Consequently, the application of local wisdom in education not only produces academically competent learners but also individuals who are culturally grounded and socially responsible.